Ireland : Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2014)
This Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision on Ireland reflects the regulatory and supervisory framework in place as of the date of the assessment. This assessment has been prepared according to the Revised Core Principles Methodology issued by the Basel Committee of Banking Supervision (BCBS). The Irish authorities chose to be assessed against the Essential and Additional Criteria but to be graded against only the Essential Criteria. Although there is no observed interference, the legislation provides for the approval of the Minister for Finance for: setting the levy structure to fund supervision, denying a license application, involuntary revocation of a banking license. The Central Bank of Ireland (CBI) undertakes supervisory activities to understand the overall structure of the banking group for which it is ultimately responsible and supervises and monitors material activities (including nonbanking activities conducted by entities in the wider group, both domestic and cross-border.